Spatial dissection of the Arabidopsis thaliana transcriptional response to downy mildew using Fluorescence Activated Cell Sorting - Coker, Timothy L.; Cevik, Volkan; Beynon, Jim L.; Gifford, Miriam L. (Frontiers in Plant Science, 2015)
Changes in gene expression form a crucial part of the plant response to infection. In the last decade, whole-leaf expression profiling has played a valuable role in identifying genes and processes that contribute to the interactions between the model plant Arabidopsis thaliana and a diverse range of pathogens. However, with some pathogens such as downy mildew caused by the biotrophic oomycete pathogen Hyaloperonospora arabidopsidis (Hpa), whole-leaf profiling may fail to capture the complete Arabidopsis response encompassing responses of non-infected as well as infected cells within the leaf. Highly localized expression changes that occur in infected cells may be diluted by the comparative abundance of non-infected cells. Furthermore, local and systemic Hpa responses of a differing nature may become conflated. To address this we applied the technique of Fluorescence Activated Cell Sorting (FACS), typically used for analyzing plant abiotic responses, to the study of plant-pathogen interactions. We isolated haustoriated (Hpa-proximal) and non-haustoriated (Hpa-distal) cells from infected seedling samples using FACS, and measured global gene expression. When compared with an uninfected control, 278 transcripts were identified as significantly differentially expressed, the vast majority of which were differentially expressed specifically in Hpa-proximal cells. By comparing our data to previous, whole organ studies, we discovered many highly locally regulated genes that can be implicated as novel in the Hpa response, and that were uncovered for the first time using our sensitive FACS technique.